2020
DOI: 10.1155/2020/7178123
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Polydatin on Jejunal Mucosal Integrity, Redox Status, Inflammatory Response, and Mitochondrial Function in Intrauterine Growth-Retarded Weanling Piglets

Abstract: Intrauterine growth retardation (IUGR) delays the gut development of neonates, but effective treatment strategies are still limited. This study used newborn piglets as a model to evaluate the protective effect of polydatin (PD) against IUGR-induced intestinal injury. In total, 36 IUGR piglets and an equal number of normal birth weight (NBW) littermates were fed either a basal diet or a PD-supplemented diet from 21 to 35 days of age. Compared with NBW, IUGR induced jejunal damage and barrier dysfunction of pigl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 56 publications
5
25
0
Order By: Relevance
“…Another interesting observation is that the percentage of goblet cells did not increase in the IUGR animals between postnatal day 7 and 14, as is the case in their normal littermates, which further confirms that the development of the gut mucosa is delayed in the IUGR piglets. As recently suggested by Zhang and co-workers [ 22 ], this delay probably ends after weaning. The decreased percentage of goblet cells in the neonatal period leads to a decreased secretion of mucins, the major product of goblet cells, thereby enhancing the likelihood of an increase in bacterial adhesion to the intestinal epithelium [ 10 , 20 , 22 ].…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Another interesting observation is that the percentage of goblet cells did not increase in the IUGR animals between postnatal day 7 and 14, as is the case in their normal littermates, which further confirms that the development of the gut mucosa is delayed in the IUGR piglets. As recently suggested by Zhang and co-workers [ 22 ], this delay probably ends after weaning. The decreased percentage of goblet cells in the neonatal period leads to a decreased secretion of mucins, the major product of goblet cells, thereby enhancing the likelihood of an increase in bacterial adhesion to the intestinal epithelium [ 10 , 20 , 22 ].…”
Section: Discussionsupporting
confidence: 56%
“…As recently suggested by Zhang and co-workers [ 22 ], this delay probably ends after weaning. The decreased percentage of goblet cells in the neonatal period leads to a decreased secretion of mucins, the major product of goblet cells, thereby enhancing the likelihood of an increase in bacterial adhesion to the intestinal epithelium [ 10 , 20 , 22 ]. Huang et al found that 12 h after birth, IUGR and normal neonates already display distinct differences in bacterial colonization, which, along with the delayed maturation of enterocytes, may constitute an early factor promoting enteritis in IUGR animals [ 20 ].…”
Section: Discussionsupporting
confidence: 56%
“…It is released into the blood and enters the intestinal tract when the intestinal mucosa is injured or necrotic. Therefore, plasma DAO activity may reflect intestinal mucosal integrity [ 23 ]. In this study, DSS markedly augmented the plasma LPS abundance and DAO activity compared to the control treatment.…”
Section: Resultsmentioning
confidence: 99%
“…In healthy individuals, the intact intestinal mucosa acts as a barrier in preventing entry of LPS and DAO into the portal circulation [ 22 , 23 ]. Chronic colitis in IBD consistently demonstrates increased intestinal permeability.…”
Section: Discussionmentioning
confidence: 99%
“…Polydatin may alleviate mucosal oxidative stress and immunological damage and may improve the intestinal epithelium barrier. 46,47…”
Section: Discussionmentioning
confidence: 99%